Hydraulic Model Study of a Water Intake under Frazil Ice Conditions - Tantillo,Thomas J (1981)
A 1:24 scale hydraulic model study of a water intake under frazil ice conditions is presented. The intake, located 9 m below the surface of the St. Lawrence River in Massena, New York, has a through flow of 0.14 cu m/s. The model study, conducted in the refrigerated flume facility of the U.S. Army Cold Regions Research and Engineering Laboratory, investigated methods of minimizing the frazil ice blockage on the intake. Two protective structures were modeled and the relative benefits of each are presented. The additional cross-sectional area provided by the protective structures lowered the vertical velocity component of the intake water to 0.0027 m/s. At this velocity the buoyant force acting on the frazil ice particle is larger than the downward drag force, causing the particle to rise. The results demonstrate that under certain low flow conditions a protective structure can minimize frazil ice blockage problems. (Author)